English Literacy Errors in Students’ Reading Comprehension at SMPN 34 Medan : Penelitian - Reny Madhani; Nurlaili; Azhary Tambusai; Wariyati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This reaserch aimed to analyze the English literacy errors made by eighth-grade students at SMPN 34 Medan in understanding narrative texts. Using a descriptive qualitative method, the research analyzed students’ written responses to a narrative text titled “The Little One and the Rain.” The findings revealed three main types of errors: inference errors (30%), vocabulary errors (30%), and referencing errors (40%). These results indicated that students struggled to interpret implied meanings, select appropriate vocabulary, and use pronouns correctly. It was concluded that teachers need to emphasize reading strategies, contextual vocabulary development, and cohesion through referencing practice to improve students’ reading comprehension.